Mindfulness and its relationship with psychological well-being among gifted student-athletes - Khalid Hammouri; Mahmoud R Azam; Amr Mohmed Soliman (CV. FOUNDAE, 2026)
Background: This study examined the level of mindfulness and its relationship with psychological well-being among gifted student-athletes in Jordan, in light of the growing interest in the psychological role of mindfulness in supporting academic and athletic performance, as well as emotional balance, among this population. Aims: The study aimed to identify levels of mindfulness and psychological well-being among gifted student-athletes, to explore the nature of the relationship between these two variables, and to examine whether statistically significant differences in psychological well-being exist by gender. Methods: The study sample consisted of 145 male and female gifted student-athletes, selected using simple random sampling. Ryff’s Psychological Well-Being Scale – Short Form was employed. Data were analyzed using appropriate statistical methods, including means and standard deviations, tests of difference, and correlation coefficients. Results: The findings indicated moderate levels of mindfulness (M = 3.22, SD = 0.35) and psychological well-being (M = 3.17, SD = 0.54). No statistically significant gender differences in psychological well-being were found (p > 0.05). In contrast, a strong, positive, and statistically significant correlation was identified between mindfulness and psychological well-being. Conclusion: The results highlight the practical value of integrating mindfulness-based training programs within educational and athletic environments for gifted students, as these programs enhance emotional balance, psychological resilience, and athletic performance. The study also provides a theoretical contribution by clarifying the relationship between mindfulness and psychological well-being within the Arab context, thereby supporting the development of evidence-based educational and athletic practices.